2019
DOI: 10.3748/wjg.v25.i30.4148
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer surveillance in inflammatory bowel disease: Practice guidelines and recent developments

Abstract: Patients with long-standing inflammatory bowel disease (IBD) involving at least 1/3 of the colon are at increased risk for colorectal cancer (CRC). Advancements in CRC screening and surveillance and improved treatment of IBD has reduced CRC incidence in patients with ulcerative colitis and Crohn’s colitis. Most cases of CRC are thought to arise from dysplasia, and recent evidence suggests that the majority of dysplastic lesions in patients with IBD are visible, in part thanks to advancements in high definition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(83 citation statements)
references
References 74 publications
1
81
0
1
Order By: Relevance
“…Numerous studies have shown that inflammatory bowel diseases (IBDs), including Crohn’s disease and ulcerative colitis (UC), are associated with the development and progression of CRC [ 4 , 5 , 6 ]. It has been reported that 25% of patients with IBD have colon cancer [ 7 , 8 ]. Based on the evidence of a strong association between IBD and CRC, colitis-associated cancer (CAC) has been proposed and is currently recognized as a special subtype of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that inflammatory bowel diseases (IBDs), including Crohn’s disease and ulcerative colitis (UC), are associated with the development and progression of CRC [ 4 , 5 , 6 ]. It has been reported that 25% of patients with IBD have colon cancer [ 7 , 8 ]. Based on the evidence of a strong association between IBD and CRC, colitis-associated cancer (CAC) has been proposed and is currently recognized as a special subtype of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…First-degree relatives of CRC patients have a threefold greater risk of developing CRC than individuals without familial predisposition. Patients with inflammatory bowel diseases are also at an increased risk of CRC [39]. The prognosis of CRC depends largely on the cancer stage at the time of diagnosis.…”
Section: Colorectal Cancer: An Overviewmentioning
confidence: 99%
“…In addition, inflammatory bowel disease (IBD) and chronic colitis have also been associated with an increased risk of CRC development (10,11). However, improved anti-inflammatory treatments and increased surveillance have been effective in reducing CRC incidence for these patients (12).…”
Section: Introduction Colorectal Cancer-epidemiology Pathophysiologymentioning
confidence: 99%